"THE IMPACT OF HUMAN ACTIVITIES ON THE ENVIRONMENT" - Rustamova Adash Eshankulovna; Nasirova Nigina (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: Human activities have increasingly influenced the environment, leading to serious and often irreversible consequences. Industrialization, deforestation, overuse of fossil fuels, intensive agriculture, and improper waste management have contributed significantly to environmental degradation. These actions have triggered global challenges such as climate change, biodiversity loss, water and soil pollution, and public health issues. Understanding these impacts is crucial for promoting sustainable living and protecting the Earth for future generations. This article explores the main human activities that damage the environment, the resulting consequences, and proposes practical solutions such as adopting renewable energy, reforestation, sustainable farming, effective waste management, and environmental education to mitigate these effects.